Participatory Journal Management Workshop: a Holistic Approach to Improving Editor Competence for National Accreditation - Nisa, Rofiatun; Supriadi, Iyus (TAAWUN, 2025)
This community service activity aims to improve the competence of scientific journal editors at Billfath University in meeting national accreditation standards. The method used is an intensive workshop based on a participatory approach, involving technical training, practical simulations, and direct mentoring. The results of the activity showed a significant improvement in the participant's ability to manage journals based on the Open Journal System (OJS), editorial governance, and accreditation achievement strategies. Participants also showed high satisfaction with the relevance and quality of the training provided. The real impact of this activity includes the implementation of more professional journal management, the formation of a community of editors network, and the creation of a more quality publication culture in the academic environment. This service makes an important contribution in supporting the sustainability of the management of credible and competitive scientific journals. Many journal managers in Indonesia lack participatory training programs that combine practical simulations with the formation of an editor community network. The results of the evaluation showed a high level of participant satisfaction, with 90% satisfied with the relevance of the material and 88% stating a significant improvement in journal management skills.